ANALISIS DAYASAING DAN DAMPAK KEBIJAKAN PEMERINTAH TERHADAP KOMODITAS KAKAO PTPN VIII KEBUN CIKUMPAY AFDELING RAJAMANDALA BANDUNG - Fitriyani Mir`ah Aliyatillah; Nunung Kusnadi (Magister Science of Agribusiness, Department of Agribusiness, FEM-IPB University, 2011)
Cocoa is one of Indonesia's export commodities that potential to be developed because the world's cocoa consumption increases year by year. However, the national cocoa facing various problems, especially the quality is still low. PTPN VIII Cikumpay Afdeling Rajamandala is national plantation that produces cocoa with quality in national standards, so the objectives of this study are to analyze competitiveness of cocoa in PTPN VIII Cikumpay Rajamandala, to analyze government policy effect, to analyze the changing effect of productivity, price of cocoa, and exchange rates of rupiah against competitiveness of the cocoa. The methods of this research are Policy Analysis Matrix (PAM) and sensitivity analysis. The results suggest that cocoa from PTPN VIII Rajamandala have competitiveness because the value of Private Cost Ratio (0.92) and Domestic Resource Cost (0.95) less than one and the value of private and social benefits are positive. The value of NPCO (Nominal Protection Coefficient Output) indicates that government policy is support competitiveness of cocoa, but the value of NPCI (Nominal Protection Coefficient on Inputs) shows that government policy is not support competitiveness of cocoa. Sensitivity analysis indicates that productivity, the price of cocoa, and exchange rate of rupiah affect the competitiveness of cocoa in PTPN VIII Cikumpay Rajamandala. Therefore, to increase productivity and to anticipate price and currency fluctuations in world markets, there should be serious steps such as the role of the government by issuing policies that protect domestic producers so the Indonesian cocoa more competitive.